Comparative Antagonistic Profiling of Different Trichoderma Species Against Drechslera tetramera, Pathogenic to Capsicum frutescens - Mohd. Adil Hussain, Adarsh Pandey and (Journal of Phytology, 2010)
Integrated Pest Management (IPM) is much popular among farmers in combating diseases of the crop. Being eco-friendly, safe and effective disease control agents, biological agents are being used widely by farmers in combating diseases and pests. Two isolates of Biological Control Agents viz. Trichoderma viride and Trichoderma harzianum were evaluated in vitro for their antagonistic profiling against Drechslera tetramera isolated from Capsicum frutescens. Both species of Trichoderma were almost equally effective against the pathogen growth in vitro. Trichoderma was found to be a potent bioagent in controlling the growth of Drechslera tetramera.